2012
DOI: 10.1051/0004-6361/201118266
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced star formation rates in AGN hosts with respect to inactive galaxies from PEP-Herschelobservations

Abstract: We compare the average star formation (SF) activity in X-ray selected AGN hosts with a mass-matched control sample of inactive galaxies, including both star forming and quiescent sources, in the 0.5 < z < 2.5 redshift range. Recent observations carried out by PACS, the 60−210 μm photometric camera on board the Herschel Space Observatory, in GOODS-S, GOODS-N and COSMOS allow us to obtain an unbiased estimate of the far-IR luminosity, and hence of the SF properties, of the two samples. Accurate AGN host stellar … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
180
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 211 publications
(214 citation statements)
references
References 176 publications
31
180
2
Order By: Relevance
“…It is clear that the 3CR FIR-detected objects have, on average, SFRs comparable to those of their equally massive non-AGN counterparts. The majority of FIRdetected objects are thus also located near the main sequence of star-forming galaxies, similarly to what has been found in deep Herschel/PACS studies of less powerful, X-ray selected, high-z AGN Santini et al 2012;Rosario et al 2013). In comparison to the FIR-detected objects, the nondetected objects have similar stellar mass but significantly lower Fig.…”
Section: Agn Versus Non-agn Host Galaxiessupporting
confidence: 75%
“…It is clear that the 3CR FIR-detected objects have, on average, SFRs comparable to those of their equally massive non-AGN counterparts. The majority of FIRdetected objects are thus also located near the main sequence of star-forming galaxies, similarly to what has been found in deep Herschel/PACS studies of less powerful, X-ray selected, high-z AGN Santini et al 2012;Rosario et al 2013). In comparison to the FIR-detected objects, the nondetected objects have similar stellar mass but significantly lower Fig.…”
Section: Agn Versus Non-agn Host Galaxiessupporting
confidence: 75%
“…It seems that AGN evolution is dominated by a nonmerger process. Other studies about AGN hosts reach similar conclusions, such as Kocevski et al (2012), Santini et al (2012), and Schawinski et al (2011). Their results provide evidence that the starburst galaxies only account for 10% of the cosmic SFR density at z ∼ 2 (Rodighiero et al 2011;Lamastra et al 2013).…”
Section: Introductionsupporting
confidence: 64%
“…Combining these results with the results of the previous section, it becomes apparent that not only are starbursts more common in those galaxies that host all types of AGN, but the starbursts occurring in those galaxies are considerably more powerful than the average starburst at all redshifts. Such a trend is also seen in AGN hosts selected by a variety of other methods (e.g., Santini et al 2012;Gruppioni et al 2013), which suggests this phenomenon is common among nearly all types of AGN.…”
Section: Starburst Strengths Of Agn Hostsmentioning
confidence: 76%
“…Already, observations from Herschel have been used to great effect to investigate the relationship between various types of AGN and their starbursting host galaxies. In galaxies with X-ray-selected AGN, numerous studies have found correlations between the strength of the starburst in galaxies, as determined by Herschel, and the strength of the AGN they host (Shao et al 2010;Harrison et al 2012b;Rovilos et al 2012;Santini et al 2012; though for an alternative viewpoint see Page et al 2012). The host galaxies of radio-and IR-selected AGN have also been the subjects of investigation with Herschel (e.g., Hardcastle et al 2012;Del Moro et al 2013), though the connection between these AGNs and their host galaxies is less clear than in the case of X-ray-selected AGN.…”
Section: Introductionmentioning
confidence: 99%